Countermeasures for Developing the Wuyi Rock Tea Industry in Fujian Province in the Post-COVID-19 Era - Wang, Yanyu; Shi, Wei (Journal of Applied Business and Economics, 2023)
As a famous variety of oolong tea in Fujian Province, Wuyi Rock Tea enjoys high brand recognition nationwide for its unique field and complex tea-making process. However, the production and sales of tea commodities were significantly affected by the global outbreak of the COVID-19 pandemic in 2019. The market for Wuyi Rock Tea was hit heavily by consumers’ reduced income and the closure of small and medium-sized enterprises. In response to the problems of Wuyi Rock Tea, it proposes countermeasures from the perspectives of cultivation, tea-making processes, market expansion, and brand promotion.